New economy, new myth - Gadrey, J. (London ; New York : Routledge, 2003)
'New economy' has been criticised greatly of late, and after the speculation and hype that surrounded the internet bubble, this is hardly surprising. This book, first published in French and updated here, however treats the 'new economy' as a discourse - one that is often misleading. In order to understand what happened during the internet bubble and the fuss that surrounded it, a central element - intellectual speculation - needs to be understood. New Economy, New Myth treats this speculation as a form of 'ultra-free-market' thinking. According to this line of thought, the internet and the digital revolution are acting as a sort of Trojan horse in spreading market deregulation across the globe. With so much having been written about the new economy, this book employs a mixture of academic rigour and readable prose and comes as a welcome relief. It will be an intriguing read for those interested in the internet bubble - and the hyperbole that surrounded it.
Translation of: Nouvelle économie, nouveau mythe.
Includes bibliographical references (p. [131]-141) and index.
aia 04/08/16
Loans
Keywords: Capitalism; Information society - Economic aspects; Information technology - Economic aspects; Economic history; Economic development